DETERMINATION OF THE VENTILATORY ANAEROBIC THRESHOLD BY THE RESPONSE OF THE HEART RATE OF INDIVIDUALS WITH RISK FACTOR FOR CARDIOVASCULAR DISEASES: COMPARISON WITH A VISUAL METHOD. - AMARAL FERREIRA, BÁRBARA; VALVERDE REIS, HUGO; NASSER, IGOR; REGUFE, VICTOR; BASTELS, RHENAN; DE OLIVEIRA MORAES, GLAUCIA MARIA; SILVA REIS, MICHEL (Journal of Respiratory & Cardiovascular Physical Therapy, 2020)
Introduction: Cardiovascular diseases (CVD) are the leading cause of death worldwide. The sedentary lifestyle stands out as one of the main risk factors related to CVD. A thorough evaluation must be carried out to prescribe properly, respecting the biological individuality. Cardiopulmonary exercise test (CPET) is a useful tool in determining functional capacity. The ventilatory anaerobic threshold (VAT) is shown as an important parameter for exercise prescription. The gold standard method for obtaining VAT is a visual analysis of the curves obtained from the ventilatory variables of the CPET. However, analysis of heart rate (HR) response appears as a promising strategy as a useful, simple and low-cost tool for determining VAT. Objective: To evaluate the validity of the VAT determination through the HR response during the CPET. Methods: Men and women were recruited, aged over 18 years and who presented risk factors for CVD. All volunteers underwent a clinical evaluation and the CPET through an incremental power protocol (10W/min) until physical exhaustion. The VAT was determined by the graphical visual method and by the heteroscedastic statistical model, where the variables time, power, HR and oxygen consumption (VO2) were analyzed. Results: No signiYicant differences were found in VO2 (mL/kg/min), VO2 (L/min) and power (W) values, comparing the determined methods. In addition, for all variables, strong correlations were found. Conclusion: The determination of VAT by the HR response proved to be an adequate model.